Redefining genocide: settler colonialism, social death and ecocide - Short, Damien (Zed Books, 2016)
Introduction -- Definitional conundrums : a sociological approach to genocide -- The genocide-ecocide nexus -- Palestine / with Haifa Rashed -- Sri Lanka / with Vinay Prakash -- Australia -- Tar sands and the indigenous peoples of northern Alberta / with Jennifer Huseman -- Looking to the future : where to from here? -- Conclusion.